The consumption of Indonesian local food and its relationship with body mass index among female university students - Nurnaningsih Herya Ulfah; Pokkate Wongsasuluk (International Journal of Public Health Science (IJPHS), 2022)
The study aimed to determine trend of Indonesian local food consumption and its association with body mass index (BMI) among female university students. It was cross-sectional study that involved 217 Indonesian female university students (18-25 years old) in April-May 2021 using conventional sampling by a self-administered online questionnaire in Malang City, East Java, Indonesia. Sociodemographic and dietary habits were collected along with body BMI data. Descriptive and Ordinal Logistic Regression were applied to analyze the data. The results showed the average BMI of 217 participants was 21.28+3.30 kg/m2. From 167 local Indonesian food that were identified, local cuisine with high carbohydrates and sugar such as fried noodles, meatballs, mixed vegetable soup, biscuits/pastry, fritters with topping, and iced milk tea with topping had a positive impact on overnutrition. Interestingly, chicken porridge had an inverse association with overnutrition. The ordinal regression results depicted the length of stay in study area had a significant association with BMI. However, meal frequency and snack time consumption also affected BMI. The preferred high-carbohydrate food is significantly associated with overnutrition (p<0.05). It is crucial to adjust nutritional education and people's food menu in reducing high-carbohydrate and sugar food to provide healthy food for university students.